2017
DOI: 10.1080/13645706.2017.1304964
|View full text |Cite
|
Sign up to set email alerts
|

Use of natural user interfaces for image navigation during laparoscopic surgery: initial experience

Abstract: The presented NUIs are feasible to directly interact in a more intuitive and sterile manner with the preoperative images and the integrated OR functionalities during laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Of the 86 articles identified, 43 (50%) were on MK, 31 (36%) were on the LMC, 2 compared MK with the LMC [77,113], 1 compared the LMC with the Myo armband [58], 1 compared MK with the LMC and the Myo armband [52], 6 were on web, video, or commercial cameras (7%), and 2 reviewed gesture interaction in general [59,65]. The data and detailed information on the studies reviewed are shown in Tables 1-3 (see Multimedia Appendices 1-3 for the full Tables 1-3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 86 articles identified, 43 (50%) were on MK, 31 (36%) were on the LMC, 2 compared MK with the LMC [77,113], 1 compared the LMC with the Myo armband [58], 1 compared MK with the LMC and the Myo armband [52], 6 were on web, video, or commercial cameras (7%), and 2 reviewed gesture interaction in general [59,65]. The data and detailed information on the studies reviewed are shown in Tables 1-3 (see Multimedia Appendices 1-3 for the full Tables 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…In the 5 ethnographic studies included, the aim was to identify interactions between the staff and gesture-based COTS systems in interventional radiology departments or in the operating room [19,59,65,78,114]. In 4 studies, the aim was to compare the performance of MK with that of a mouse [5,79,80,96]; in 1 study, it was to compare the performance of the LMC with that of a mouse [81]; and in 4 studies, it was to compare different COTS devices [52,58,77,113]. In 10 studies, the aim was to evaluate face validity [97,120], content validity [97], construct validity [66,110,111,120,121,126,127,132], or concurrent validity of the devices [66,71,121,126].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Devices for gesture-based human-computer interaction are a new way of interacting with virtual environments. This study’s simulator presents a new form of gesture-based simulation that is portable, low-cost, and enables ubiquitous learning and preoperative warm-up [ 14 , 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%